THE RIGHTEOUS STATE IN BUDDHISM, AS ARTICULATED IN SELECTED DISCOURSES FROM THE SUTTA PIṬAKA - Dhammarakkhitha, Rev Morawaka (Jurnal Pencerahan, 2024)
This research aims to critically examine the righteous State in Buddhism as articulated in the selected discourses from the Sutta Piṭaka. Through qualitative research methodology with library approach, this research was carried out by collecting data from primary sources and secondary sources. This research shows that according to Buddhism, righteous State is not only as a good governance, but also include the righteous people in the society. It is understood that even though, Buddhism directly shows the path to get rid of existence (saṃsāra), but the Buddha and his disciples lived in society. Therefore, the Buddha tried to promote social virtues, duties and responsibilities necessary for a better social pattern. The Anukampaka, Vyagghapajja and Sigālovāda discourses include the teachings required to secure social values. According to the Rajja Sutta of Saṃyutta Nikāya, the Buddha’s attitude was to see a governance that does not kill or harm others. The Buddha preached the king Kosala once that there is no real winner in war, and it destroys social harmony as well. So, Buddhism focuses not only on creating a good governance, but also a society with moral people, and building a good State in the combination of both.